2016
DOI: 10.1016/j.jtcvs.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of desmin-mitochondrial architecture in patients with regurgitant mitral valves and preserved ventricular function

Abstract: Objective-Recent studies have demonstrated improved outcomes in patients receiving early surgery for degenerative mitral valvular regurgitation (MR) rather than adhering to conventional guidelines for surgical intervention. However, studies providing a mechanistic basis for these findings are limited. Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…Myofibrillar breakdown has been reported in the human with chronic isolated MR [9, 23] and in the dog [18] with experimentally-induced chronic MR by hematoxylin and eosin staining and transmission electron microscopy. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myofibrillar breakdown has been reported in the human with chronic isolated MR [9, 23] and in the dog [18] with experimentally-induced chronic MR by hematoxylin and eosin staining and transmission electron microscopy. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to an increase in mast cells in VO, we have demonstrated fibroblast production of chymase that results in intracellular autophagic breakdown of procollagen and fibronectin in the rat [6]. There is also a concomitant breakdown of cardiomyocyte myofibrils and the major intermediate filament desmin [7, 8, 9]. Thus, extracellular and intracellular structural protein breakdown is the underpinning of cardiomyocyte elongation and thinning that translates to LV spherical dilatation and wall thinning.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue analysis. Transmission electron microscopy (TEM) was performed as previously described in our laboratory (EMLabs, Birmingham, AL) (6,21). Immunoblots on cardiac tissues were performed according to previously described methods using previously validated antibodies (4).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Mankad et al showed with CMR tagging abnormal regional strain patterns in patients with severe MR and preserved LV ejection fraction: while radial strain was increased (19 ± 9 vs. 16 ± 6%, p = 0.003), circumferential strain was reduced (12 ± 6 vs. 21 ± 6%, p ≤ 0.001) as compared to healthy controls [ 71 ]. Several authors have demonstrated a decrease in global longitudinal and circumferential strain parameters on CMR tagging in patients with severe degenerative MR after mitral valve repair, which might imply an ongoing myocardial fibrosis after surgery [ 72 74 ].…”
Section: Cmr Left Ventricular Myocardial Fibrosis Assessment In Vhd: mentioning
confidence: 99%